2013
DOI: 10.4236/fns.2013.44061
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Bioconversion for Producing Common Bean (<i>Phaseolus</i> <i>vulgaris</i> L.) Functional Flour with High Antioxidant Activity and Antihypertensive Potential

Abstract: The main objective of this investigation was to study the time effect during solid state bioconversion (SSB) on total phenolics content (TPC) and antioxidant activity (AoxA) of common beans to improve antihypertensive functionality. Cooked cotyledons of dehulled common beans were inoculated with a suspension of R. oligosporus NRRL 2710 (1 × 10 6 spores/mL), and incubated at 35˚C for times of 24,36,48,60, 72, 84, 96 and 108 h (after 108 h the cotyledons showed off odor). Flours from bioprocessed dehulled commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
(47 reference statements)
2
12
1
Order By: Relevance
“…Contrary to those reported by Guzmán-Uriarte et al (2013) and in relation to Reyes-Bastidas et al (2010), our results have shown that shorter fermentation times increased the concentration of polyphenols. The latter could also be related to the native cultivar composition.…”
Section: Phenolic Concentration Of Common Bean Tempeh Flourcontrasting
confidence: 56%
See 2 more Smart Citations
“…Contrary to those reported by Guzmán-Uriarte et al (2013) and in relation to Reyes-Bastidas et al (2010), our results have shown that shorter fermentation times increased the concentration of polyphenols. The latter could also be related to the native cultivar composition.…”
Section: Phenolic Concentration Of Common Bean Tempeh Flourcontrasting
confidence: 56%
“…For example, the highest concentration of these compounds in BV was shown by T3540, whereas for PD tempeh was in T3040. Reyes-Bastidas et al (2010) reported a lower concentration of phenolic compounds in tempeh from common beans using fermentation conditions of 34.9C and 51 h. However, Guzmán-Uriarte et al (2013) reported higher values at 35C and 108 h of fermentation time. In both cases, the temperature promoted the β-glucosidase production by fungi, which contributed to the valid conversion to aglycones, increasing the TPC of samples.…”
Section: Phenolic Concentration Of Common Bean Tempeh Flourmentioning
confidence: 96%
See 1 more Smart Citation
“…, 1996). There are similar reports when using R. oligosporus and various substrates: mix corn/soybean (Mugula & Lyimo, 2000); soybean (Ruíz-Terán & Owens, 1996), quality protein maize and common bean (Guzmán-Uriarte et al, 2013). Dehulling chickpea decrease the content of ash and fiber mainly as a consequence of hulls containing certain minerals (calcium, phosphorus, magnesium, iron, potassium) and a high concentration of fiber (Laurena et al, 1986;Williams & Singh, 1987).…”
Section: Discussionmentioning
confidence: 71%
“…It yields high quality products with a minimal degradation of nutrients, and has a significant improvement in digestibility and biological value of proteins (CuevasRodríguez et al, 2004;Guzmán-Uriarte et al, 2013). It has also been proved that fermentation induce favorable changes in the legumes antinutrients, such as reduction in the activity of enzymatic inhibitors (i.e.…”
Section: Introductionmentioning
confidence: 99%